On hermeneutical openness and wilful hermeneutical ignorance - Landström, Karl (Labyrinth, 2022)
In this paper I argue for the relevance of the philosophy of Hans-Georg Gadamer for contemporary feminist scholarship on epistemic injustice and oppression. Specifically, I set out to argue for the Gadamerian notion of hermeneutical openness as an important hermeneutic virtue, and a potential remedy for existing epistemic injustices. In doing so I follow feminist philosophers such as Linda Martín Alcoff and Georgia Warnke that have adopted the insights of Gadamer for the purpose of social and feminist philosophy. Further, this paper is positioned in relation to a recent book chapter by Cynthia Nielsen and David Utsler in which they argue for the complementarity, and intersecting themes and concerns of Gadamer's hermeneutics and Miranda Fricker's work on epistemic injustice. However, Nielsen and Utsler solely focus on Fricker's conception of epistemic injustice and the two forms of epistemic injustice, testimonial injustice and hermeneutical injustice, that she identifies. In this paper I expand their analysis by considering other forms of epistemic injustice such as wilful hermeneutical ignorance and contributory injustice. Thus, this paper contributes to the budding literature on the relevance of Gadamer's work for the debates pertaining to epistemic injustice and oppression by expanding such analysis to other forms of epistemic injustice, and by further arguing for the strength of Gadamer's work in terms of offering relevant insights for the reduction and remedy of existing epistemic injustices.